Gingival and Salivary Changes in Correlation with Multiple Sclerosis (Medico Legal Update, 2020)
Multiple sclerosis: chronic degenerative autoimmune disease of the central nervous system marked by patchy destruction of the myelin sheath that surrounds the nerve fibers. The gingival or oral changes that associated with multiple sclerosis might be related to disease itself or as sequel of medications that used for treatment. Aims;-to determine the gingival index and assess the SIgA, SFR and PH in MS patients in compare to control group as well as analyses theses parameters according to age group, gender and type of MS. 36 patients with proven diagnosis of MS were selected randomly between 1st Nov.2016-1st nov.2017 from MS center. Medical city .Baghdad. Iraq. Oral examination was done to measure the gingival index as well as saliva was taken to assess the salivary IgA level, salivary flow rate and PH of saliva, in addition 20 subjects who are free of MS or any others autoimmune disease were selected as control group. The GI of patients group was significantly higher than control group(3.4 ,1.4) respectively while the SIgA ,SFR and PH of saliva was significantly lower with patients group in compare to control group510,0.56,6.6 for patients group) 941.8,1.7,7.1 for control group